IoT based dual axis solar tracker implementation for polycrystalline photovoltaic with energy storage - Abu Hassan, Omar; Hamdani, Hazwani; Hashim, Hairulazwan; Ma’ Radzi, Ahmad Al’abqari; Ahmad, Muhammad Shukri; Tengku Ibrahim, Tengku Nadzlin; Zulkifli, Shamsul Aizam (FAZ Publishing, 2020)
This project has been identified as IoT Based Dual Axis Solar Tracker Implementation for Polycrystalline Photovoltaic with Energy Storage that has two degrees of freedom that act as axes of rotation, both horizontal and vertical. Polycrystalline panel is great in both diffuse light and specular light and yet known for its minimal cost. This motorized servo-motor system based final year project is a self-orient the solar panel towards the maximum intensity of sunlight using Light Dependent Resistor (LDR) and hence, it will generate supply to the load. The main system that use to control the movement of motor and sense the LDR is Arduino Uno. This portable 10W solar project can be used anywhere at any time as its main concern to educate people of basic solar tracker concept aside to help supplying 5V Direct Current (DC) load. An Internet of Things (IoT) is therefore added as a feature for this project to monitor the performance of photovoltaic voltage through Blynk application in cell phone